X-ray magnetic dichroism and tunnel magneto-resistance study of the magnetic phase in epitaxial CrVOx nanoclusters. (27th April 2022) - Joly, Loïc; Scheurer, Fabrice; Ohresser, Philippe; Kengni-Zanguim, Brice; Dayen, Jean-François; Seneor, Pierre; Dlubak, Bruno; Godel, Florian; Halley, David
Abstract: Epitaxial clusters of chromium and chromium–vanadium oxides are studied by tunnel magneto-resistivity measurements, x-ray absorption spectrometry and circular magnetic circular dichroism. They turn out to carry a small magnetic moment that follows a super-paramagnetic behavior. The chromium ion contribution to this magnetization is mainly due to an original magnetic Cr2 O3 -like phase, whereas usual Cr2 O3 is known to be anti-ferromagnetic in the bulk. For mixed clusters, vanadium ions also contribute to the total magnetization and they are coupled to the chromium ion spins. By measuring the dichroic signal at different temperatures, we get insight into the possible spin configurations of vanadium and chromium ions: we propose that the magnetic dipoles observed in the clusters assembly could be related to ionic spins that couple at a very short range, as for instance in short one-dimensional spins chains.